COVID-19: The effects of perceived organizational justice, job engagement, and perceived job alternatives on turnover intention among frontline nurses - Zhou, Lulin; Tetgoum Kachie, Arielle Doris; Xu, Xinglong; Quansah, Prince Ewudzie; Epalle, Thomas Martial; Ampon-Wireko, Sabina; Nkrumah, Edmund Nana Kwame (Frontiers in Psychology, 2022)
Nurses’ turnover intention has become a concern for medical institutions because nurses are more needed than ever under the prevalence of COVID-19. This research sought to investigate the effects of the four dimensions of organizational justice on COVID-19 frontline nurses’ turnover intention through the mediating role of job engagement. We also tested the extent to which perceived job alternatives could moderate the relationship between job engagement and turnover intention. This descriptive cross-sectional study used an online survey to collect data from 650 frontline nurses working in appointed hospitals in Jiangsu province, China. Hierarchical regression was used to analyze the hypothesized relationships. Findings revealed that all organizational justice components significantly influenced job engagement and turnover intention. Job engagement also significantly affected nurses’ turnover intention and mediated the relationships between organizational justice components and turnover intention. Besides, perceived job alternatives moderated the relationships between job engagement and turnover intention. The implications of this study include demonstrating that healthcare authorities should respect human rights through effective organizational justice as this approach could encourage nurses to appreciate their job and be more devoted to staying and achieving their institutional duties, especially under challenging circumstances.